The Ibans belief towards the meaning of Pua Kumbus motif - Magiman, Mohamad Maulana; Chelum, Alexander; Durin, Anna; Lim, Connie Keh Nie; Mohd Yusoff, Ahmad Nasir (Scholars Academic and Scientific Publishers(SAS Publishers), 2018)
This article emphasizes on the findings on the level of knowledge and perception of Pua Kumbu in young Iban generations. This includes the uses, meaning of motif and rituals related to this fabric. Factors contributing to the declining belief in using Pua Kumbu in their traditional practice were also explained. The knowledge in traditionally weaving the Pua Kumbu was mainly reserved to certain class of woman in the long house. The chosen motif was dependent on illustration that appeared in their dream, where they believe that this was a sign or omen. The rules of weaving motif were also explained. There were three significance motifs with its own hidden meaning found in Pua Kumbu; the ular (snake), antu engkeramba and baya(crocodile) which became the belief of the Iban people. This study suggests that the lack in knowledge and interest in the Pua Kumbu may come from factors such as relocation away from the long house, modernization, religion and generation gaps.